COMPOSIÇÃO QUÍMICA DO RESÍDUO DA GUAVIRA (CAMPOMENESIA ADAMANTIUM CAMBESS) - GONÇALVES, Giovana de Arruda Castelo; DIONIZIO, Bruna Gasparini; SANTOS, Vitória Trindade; SANTOS, Evellyn Richelly Ferreira; SALMAZZO, Gustavo Ruivo; PASQUETTI, Tiago Junior (ANAIS DO ENIC, 2018)
-